Virtualization Security, Key Issues of Public Cloud Computing Security - Jiaren Jiang (Dianxin kexue)
With the prosperous development of information technologies and popularity of information-based on a global basis, public application and service of cloud computing has become a trend and inevitable part of enterprise growth.Only an enterprise is speeding up the process,which is playing an increasingly important role in the enterprise growth. The security status of public cloud computing was firstly analyzed. Several important technologies were introduced, particularly concerning their dominant positions and inferior strengths. Finally, according to the in-depth research analysis and practical strategies,the protection measures for public cloud computing have been proposed.